Estudo de diferentes metodologias para avaliar o potencial de Trichoderma harzianum no controle de Sclerotinia sclerotiorum na cultura do feijoeiro - Constantino, Leonardo Pesseti (2018)
Black bean (Phaseolus vulgaris L.), is considered a major legume in human consumption, but its production is affected by environmental adversities, pests and diseases. A disease considered of great importance for this crop is the white mold (Sclerotinia sclerotiorum), being its main form of control the use of chemical agents. However, due to the requirement for better quality foods, organic products are gaining great importance, one of them being Trichoderma products, which have high control of pathogens, including white mold, but there are few studies to quantify the efficiency of field control. This present work proposes to study different methodologies to evaluate the potential of Trichoderma harzianum in the control of Sclerotinia sclerotiorum in the bean crop. The experiment was conducted on the field at Universidade Tecnológica do Paraná, Campus Dois Vizinhos, from March 12th 2018 to May 14th 2018. Black bean seeds were used without any treatment, and were conducted in soil classified as Red Latosol, with a sowing rate of 6 to 8 plants per linear meter with spacing of 0.6 meters between rows. The experimental design was randomized blocks, with 6 treatments and 4 replicates. The following treatments were used: T1 Control standard EMBRAPA (bag with sclerotia in the tray without application of Trichoderma), T2 Standard EMBRAPA (bag with sclerotia in the tray), T3 Sachet with sclerotia directly on soil, T4 Gerbox® with sclerotia, T5 Control Sachet with sclerotia directly on the ground (without application of Trichoderma) and T6 Control Gerbox® with sclerotia (without application of Trichoderma). The applications of Trichoderma were carried out in the vegetative stage V2 and V4 of the culture, after 7 days of the last application were packed in Gerbox® and incubated in BOD and later evaluated after 42 days. The variables analyzed were: number of sclerodians that returned from the field, counting the number of apothecia and number of existing stapes for each treatment. The results were evaluated for the homogeneity and normality of the residues and later submitted to analysis of variance, were grouped by the Tukey averages test at 5% error probability, using the Genes statistical program. There was no significant difference in relation to the treatments with Trichoderma on the controls, This may be due to the low viability of sclerotia due to the in vitro multiplication that gave rise to small sclerosies with low viability, also due to the environmental conditions of high temperature and high humidity that may have degraded the sclerotia in the field, or by the control of sclerotia by Trichoderma present in the soil in a natural way due to the good soil management. Further work is suggested, however using larger sclerosis with better viability and using areas with high disease infestation and having low levels of natural Trichoderma in the soil